The use of Total Maximum Daily Load (TMDL) in improving water quality of Segamat River / Faridah Mohd Razelan - Mohd Razelan, Faridah (2018)
Quality of life reduces from time to time due to un-controlled pollution. Drinking contaminated water, breathing polluted air and suffering from un-wanted noise everyday will affect human health in both short and long term basis. From the studies that had been reviewed, there are ways being introduced by researchers to overcome pollution problem. Total Maximum Daily Load (TMDL) has been introduced in this study as a method in improving the Segamat River water quality.